2015
DOI: 10.3390/ma8020408
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Membranes of PLLA/Collagen for Bone Tissue Engineering: A Comparative Study of Scaffold Production Techniques for Optimal Mechanical Properties and Osteoinduction Ability

Abstract: Synthetic and natural polymer association is a promising tool in tissue engineering. The aim of this study was to compare five methodologies for producing hybrid scaffolds for cell culture using poly-l-lactide (PLLA) and collagen: functionalization of PLLA electrospun by (1) dialkylamine and collagen immobilization with glutaraldehyde and by (2) hydrolysis and collagen immobilization with carbodiimide chemistry; (3) co-electrospinning of PLLA/chloroform and collagen/hexafluoropropanol (HFP) solutions; (4) co-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Theisen et al tested the same blend in electrospun scaffolds, and demonstrated a good proliferation of human tenoblasts from long biceps tendons [33]. Conçalves et al studied the morphology, mechanical properties and osteoblastic differentiation of random electrospun fiber scaffolds mats made by five different kinds of PLLA/Coll blends and solvents systems, confirming their good biocompatibility [34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Theisen et al tested the same blend in electrospun scaffolds, and demonstrated a good proliferation of human tenoblasts from long biceps tendons [33]. Conçalves et al studied the morphology, mechanical properties and osteoblastic differentiation of random electrospun fiber scaffolds mats made by five different kinds of PLLA/Coll blends and solvents systems, confirming their good biocompatibility [34].…”
Section: Discussionmentioning
confidence: 98%
“…Because of their inherent properties of biological recognition, natural polymers have therefore been proposed in combination with synthetic polymers for tendon reconstruction: for instance poly(L-lactide-co-ε-caprolactone) copolymer has been blended with either collagen [29] or silk [30] and chitosan and gelatin have been used in combination with poly(L-lactic acid) (PLLA) [28]. While blends of collagen and PLLA have been investigated in the past [31][32][33][34] they have never been manufactured to produce bundles for tendon reconstruction. Moreover, the effect of the amount of the natural component on the mechanical properties of the bundle and on cell behaviour, as well the stability of bundle composition under physiological condition have never been deeply investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers had tried to report the application of PLLA for soft tissue such as heart valve and blood vessel but all of them failed. Several works have been done on fabricating polymer blends such as PLLA/ PCL [32], PLLA/chitosan [33], PLLA/collagen [34], PLA/PLGA [19], and polymer composites like PLLA/hydroxyapatite (HA) and PLLA/carbon nanotubes (CNTs) [35,36], to enhance the flexibility and elasticity properties of scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…The porosity, orientation, and size of fibers and chemical affinity are essential to define the best materials to develop the ideal scaffold for optimum cells adhesion and/or BMPs adsorption. Several materials have been tested as carriers, from synthetic to natural sources, such as hydroxyapatite, bioglass, calcium sulfates, calcium phosphates, β-tricalcium phosphate, calcium carbonate, organic polymers, polylactic acid (PLA), polyglycolic acid (PGA), copolymers (such as polylactic-co-polyglycolic acid (PGLA)), methylmethacrylate, hyaluran, fibrina, alginate, silk, agarose and collagen (Carpena, Min, & Lee, 2015;Chen, Liu, Gu, Feng, & Yang, 2015;Dadsetan et al, 2015;Gonçalves et al, 2015;Margolin et al, 1998;Seeherman & Wozney, 2005). The choice of a biomaterial depends on a good compatibility, accessibility, and low immunogenicity.…”
Section: Bmps As a Bioactive Molecule For Coating Biomaterial's Surfacesmentioning
confidence: 99%